Pengaruh Supervisi Akademik, Budaya Sekolah dan Kinerja Guru Terhadap Mutu Pembelajaran di SMK Ma’arif 9 Kebumen - Kismiyati Kismiyati (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2020)
This research is based on the problem of unsatisfactory learning quality. In this regard, this study aims to determine the effect of academic supervision, school culture, and teacher performance on the quality of learning at SMK Ma'arif 9 Kebumen. This research is a quantitative research. The population and sample in this study were all teachers at SMK Ma'arif 9 Kebumen, namely 21 people. Data collection using questionnaires, and data analysis using simple linear regression analysis techniques and multiple linear regression analysis. This study resulted in the following conclusions. (1) Academic Supervision has a positive and significant influence on the Quality of Learning at Ma'arif 9 Kebumen Vocational School, as evidenced by the value of Sig = 0.048 < α = 0.05. The value of the correlation coefficient (r2) = 0.191 or a contribution of 19.1%. (2) School culture has a positive and significant influence on the quality of learning at SMK Ma'arif 9 Kebumen, as evidenced by the value of Sig = 0.007 < α = 0.05. The value of the correlation coefficient (r2) = 0.324 or a contribution of 32.4%. (3) Teacher performance has a positive and significant influence on the quality of learning at SMK Ma'arif 9 Kebumen, as evidenced by the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (r2) = 0.668 or a contribution of 66.8%. (4) Academic Supervision, School Culture, and Teacher Performance together have a positive and significant influence on the Quality of Learning at Ma'arif 9 Kebumen Vocational School, as evidenced by the value of Sig = 0.000 < α = 0.05. The value of the correlation coefficient (R2) = 0.673 or contributes 67.3%.